Injil bagi Nelayan: Sebuah Pembacaan Teologis-Maritim terhadap Markus 1:16-20 - Maggang, Elia (Veritas : Jurnal Teologi dan Pelayanan, 2024)
In the maritime country of Indonesia, fishers have significant roles, including actualising God’s providence for the Indonesian people and nature. However, in its political crisis, the fisher’s world seems ignored in theological discourse. Therefore, this article seeks to delve theologically into the meaning of the Christian Gospel (euanggelion) and its implications on the fisher’s life. In anchorage with the new meaning of the Gospel drawing from a discussion on Jesus’ calling of the four Galilean fishers to be his disciples in Mark 1:16-20, this article affirms that fishers have a place in the Gospel’s message and actualisation. Thus, the proclamation and actualisation of the Gospel must include active involvement in overcoming the crisis in the fisher’s world.